FAKTOR-FAKTOR KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN RESTORAN YEOJAFOOD DI KARANGANYAR - Novi Anarima Wahyuning Hapsari; Jumriah Basri (Paser Institute Management and Busines, 2025)
Basically, in the culinary industry, food products are a key factor that plays a major role in the success of a business. Therefore, every restaurant needs to prioritize the quality of its products so that consumers feel satisfied and the business can excel in the midst of market competition. The purpose of this study is to identify the factors of food product quality at Yeojafood Restaurant and their impact on customer satisfaction. The method used in this research is a case study with a qualitative approach. Data collection in the study was counducted through direct observation of actual conditions, as well as in-depth interviews with the owner and customers of Yeojafood Restaurant. The result showed that product quality plays a significant role maximizing customer satisfaction. Factors such as taste, number of servings, presentation appearance, and menu diversity also contribute significantly to increasing customer satisfaction. Form this study, it can be concluded that customer satisfaction is formed when perceptions of these product quality factor exceed their expectations. Optimal product quality not only creates momentary satisfaction but also encourages loyalty from customers.